Pelatihan Pembuatan Audible Books Berbasis Etnomatematika Melayu Riau Sebagai Penguatan Keterampilan Guru Membuat Buku Cerita Yang Dapat Meningkatkan Literasi Dan Numerasi untuk Siswa Sekolah Dasar - Alim, Jesi; Hermita, Neni; Putra, Zetra Hainul; Suroyo, Suroyo; Charlina, Charlina; Witri, Gustimal; Oktaviani, Cici (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
Reading is one way that can be used as a basis in shaping learning. Literacy and numeracy skills are abilities that must be possessed and become demands in 21st century learning. The service program was carried out for seven months, beginning with the completion of the program in March, and the implementation of the service in August-September. This service activity is carried out with a classical approach, namely by delivering material about Riau Malay ethnomathematics which will later be used as a reference for teachers to write stories in books that will be used as Audible Books. Based on the training that has been carried out, it is concluded that the community service activities that have been carried out are running smoothly, the teachers are also very enthusiastic and motivated in writing stories with the theme of Malay culture. From this training activity, five picture books were produced with the theme of Malay culture.